SOSIALISASI DIGITALISASI PERPAJAKAN UMKM MELALUI PENYULUHAN DAN PELATIHAN - Mulyani, Susi Dwi; Muhd. Nuryatno Amin; Ismawati Haribowo; Sistya Rachmawati (Universitas Trisakti, 2025)
Directorate General of Taxes (DGT), in the form of an online tax service application. Taxpayers can enjoy various digital services to fulfill their tax obligations. The DGT provides a single login facility, which is the gateway to 3C-based services (click-call-counter). This 3C service program provides taxpayers with a system of channels, but is not limited to these three (DGT, 2020), and is available to Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. MSMEs who are members of the Indonesian Professional Kartini Association (IKAPRI Indonesia) as partners in the Community Service activities by the Team of Lecturers, Students and Alumni of the Faculty of Economics and Business (FEB) Usakti Doctoral Program and Lecturers of STIE Tri Bhakti, have limited knowledge and understanding of digital tax applications and how to gain access to use them. Therefore, the Community Service Team of the Faculty of Economics and Business Trisakti University carried out outreach and training activities on the Socialization of MSME Tax Digitalization. The materials presented included: i) the legal basis for MSME Income Tax; ii) how to obtain an NPWP online; and iii) how to calculate, deposit, and report MSME Income Tax online. The Community Service activity was held on December 17, 2024, at the Faculty of Economics and Business (FEB) Trisakti University, with 32 MSME participants. The results of the Community Service activities have succeeded in reducing the number of participants who did not understand in operating online tax services and an increase in the number of participants who did understand in operating online tax services, with an average of 47.4%.